Tradisi Mayu Desa di Desa Pakel Kecamatan Sukapura Kabupaten Probolinggo (Tintingan Bentuk, Makna, Fungsi, dan Perubahan) - Khoiriah, Mufi Datul; Andriyanto, Octo Dendy (Jurnal Online Baradha, 2023)
Mayu Village Tradition is a gratitude of Pakel village community to Almighty God and the ancestors of Pakel village from the establishment until the present day. The Mayu Village Tradition is held once a year in the month of Ruwah with the purpose of honoring the ancestors who guard the Pakel village. In addition, the goal of Mayu Village Tradition is giving the Tengger tribe people safety, peace and protection from danger. The meaning, function, and the equipment of this village mayu event is charity crops to the ancestors and charity to the earth. This research used descriptive qualitative method that provides an overview of the meaning, function, and alteration of the Mayu Village Tradition in Pakel Village, Sukapura Subdistrict, Probolinggo Regency. The data research formed as oral data and written data. The data collection techniques used observation, interview techniques (field notes, interviews, and observation field notes), and documentation. This research has three objectives, namely behavior, meaning, and function of the Mayu Village Tradition. The equipment used for nyekar punden and Mayu Desa ceremony. The procedures in Mayu Village Tradition are opening, implementation, and closing. This tradition has meaning and function as village thanksgiving to get away from danger and can give blessings especially to the people of Pakel village, Sukapura District, Probolinggo Regency. Keyword: Mayu Village Tradition, Meaning, Equipment, Funstion.